Serum amyloid A (SAA) concentration after training sessions in Arabian race and endurance horses - Cywinska, Anna (BioMed Central, 2013)
BACKGROUND: Serum amyloid A (SAA) is the major acute phase protein in horses. Its concentration increases in various pathologies but also in response to prolonged, strenuous effort. The purpose of this study was to establish whether routine race and endurance training produces changes in the SAA level in Arabian horses. Additionally, the differences between SAA response in experienced endurance horses and endurance horses that were beginning their career were investigated. RESULTS: There were no changes in SAA concentrations after race training and endurance training in experienced horses. In horses that were beginning their endurance training, exercise produced an increase in SAA level as compared with rest level. CONCLUSION: In Arabians, the SAA concentration seems to be a good indicator of endurance training but is useless in race training. The routine training of experienced horses, which were prepared for long distance rides, did not promote any changes in the SAA level. In contrast, a significant increase in the SAA concentration was observed in horses that were beginning their endurance training and were only prepared for moderate distance rides and underwent the same effort. Further research is needed to elucidate whether this difference reflects too heavy training or adaptation to an increasing workload. Additionally, the adaptation to long distance rides in Arabians may include a reduced acute phase response.